The Studies of Buffer Control Strategy of 128 kb/s Videophone System - 王海松; 何芸 (Tongxin xuebao)
A new bit-rate control strategy with both global pre-allocation and local segmentation （GALS） for low bit rate application of Rec.H.261.is proposed in this paper. Test sequences are used to compare the proposed strategy with RM8’s by computer simulation. Experimental results show that,the proposed strategy reveals improved subjective quality.